Pengaruh Peran Komunikasi Internal, Kepemimpinan Situasional, Dan Kepuasan Kerja Dalam Meningkatkan Kinerja Karyawan Golden City Bekasi - Dania Tri Utami; Muhammad Asif Khan; Eri Bukhari (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research was used to measure the influence of internal communication, situational leadership and job satisfaction on the job satisfaction of Golden City Bekasi employees. This research uses quantitative research with a quantitative cross-sectional approach. The objects used in this research are Golden City Bekasi employees. The sample used in this research used a purposive sampling technique with the number of samples used in this research being 123 respondents. The analysis method uses outer model testing, inner model testing, and hypothesis testing using the SmartPLS 4.0 analysis tool. The results of the research that has been carried out show that: 1). Internal Communication has no effect on Employee Performance, with the overall results showing that the internal communication indicator has no effect, namely the lowest indicator of internal communication (X1.1).2). Situational Leadership has no effect on Employee Performance, with the overall results showing that the situational leadership indicators have no effect, namely from indicators (X2.4) and 3). Job satisfaction influences employee performance with the overall results showing that job satisfaction indicators play an important role in employee performance